Checklist of freshwater symbiotic temnocephalans (Platyhelminthes, Rhabditophora, Temnocephalida) from the Neotropics - Martínez Aquino, Andrés (2014)
Based on published records and original data derived from our research, we have generated a checklist of symbiotic temnocephalan fauna from 57 taxa of freshwater invertebrate and vertebrate hosts from 16 families included in four classes from the Neotropics. The checklist contains 38 nominal species from 3 genera belonging to the Temnocephalida families Diceratocephalidae, Didymorchidae and Temnocephalidae. All taxa (35) of the genus Temnocephala are endemic to the Neotropics and 14 (40%) are considered microendemic (i.e. only one record each from a single locality). While only one species and one variety of Didymorchis are known from the Neotropics; there are also two putative undescribed species of this genus. Only Diceratocephala boschmai (Diceratocephalidae) is reported as an introduced species from Uruguay. Host specificity to a particular group of invertebrates and vertebrates is the first evidence for the ecological and evolutionary associations that will be analyzed in future studies.